2017
DOI: 10.1212/wnl.0000000000004300
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging in myotonic dystrophy type 1

Abstract: Objective:To systematically review brain imaging studies in myotonic dystrophy type 1 (DM1).Methods:We searched Embase (index period 1974–2016) and MEDLINE (index period 1946–2016) for studies in patients with DM1 using MRI, magnetic resonance spectroscopy (MRS), functional MRI (fMRI), CT, ultrasound, PET, or SPECT. From 81 studies, we extracted clinical characteristics, primary outcomes, clinical-genetic correlations, and information on potential risk of bias. Results were summarized and pooled prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 54 publications
2
71
1
Order By: Relevance
“…In contrast to some previous data [11], we found that volumetric changes were generally less marked in white matter structures compared with associated grey matter. Nonetheless, white matter pathology clearly represents an important component of the CNS structural landscape in DM1, as evidenced by the frequent occurrence of T2 hyperintense lesions [10], and widespread reduced fractional anisotropy on diffusion tensor imaging, even in normal-appearing white matter [64]. It remains uncertain to what extent white matter disease represents a primary manifestation of the DM1 disease process, versus Wallerian degeneration secondary to loss of associated grey matter [16].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to some previous data [11], we found that volumetric changes were generally less marked in white matter structures compared with associated grey matter. Nonetheless, white matter pathology clearly represents an important component of the CNS structural landscape in DM1, as evidenced by the frequent occurrence of T2 hyperintense lesions [10], and widespread reduced fractional anisotropy on diffusion tensor imaging, even in normal-appearing white matter [64]. It remains uncertain to what extent white matter disease represents a primary manifestation of the DM1 disease process, versus Wallerian degeneration secondary to loss of associated grey matter [16].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, significant negative correlations were found between regional GM volumes and CTG repeat length in other studies [ 16 , 19 ]. These conflicting results may be due to differences in the detailed analysis methods, the clinical variability of the study population, the somatic mosaicism of CTG repeat lengths, or repeat number increases throughout life, even in post-mitotic tissues [ 3 , 31 ]. There are considerable tissue variations in repeat lengths, and repeat size in the blood might not correlate with that in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Further, diffusion tensor imaging (DTI) reveals the presence of diffuse, microstructural disruption even in apparently normal-looking white matter ( 27 ). Correlations have been described between impairment in specific cognitive domains or CTG repeat length with measures of gray matter volume ( 28 – 31 ), total volume of white matter lesions (VWML) ( 31 – 34 ) and DTI measures ( 29 , 31 – 36 ), although findings are inconsistent between studies, and no consensus imaging biomarker for CNS involvement has yet been identified ( 37 ).…”
Section: Introductionmentioning
confidence: 99%